Non-diffractive laser resonators - Rogel-Salazar,J; New,GHC; Chavez-Cerda,S (2000)
A Bessel-beam laser based on an optical resonator was considered and a computational model of cavity incorporating an axicon was also investigated. Parameters such as the use of plane output mirror and varied cavity length propagation were used. The simulation results confirmed the modes of the cavity as Bessel beams were simple transverse standing waves. Bessel beams representative of Hankel functions, were fundamental travelling-wave solutions of Helmholtz reduced wave equations.